2015
DOI: 10.1097/mot.0000000000000159
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell infusion/transplantation for induction of allograft tolerance

Abstract: Purpose of review This review updates the current status of basic, preclinical, and clinical research on donor hematopoietic stem cell infusion for allograft tolerance induction. Recent findings Recent basic studies in mice provide evidence of significant involvement of both central deletional and peripheral regulatory mechanisms in induction and maintenance of allograft tolerance effected through a mixed chimerism approach with donor hematopoietic stem cell infusion. The presence of heterologous memory T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 95 publications
1
14
0
Order By: Relevance
“…The level and duration of hematopoietic chimerism required to achieve transplantation tolerance have not been completely elucidated. Equally, the relative contributions of central thymic deletion versus peripheral regulatory mechanisms of host alloreactive lymphocytes to the initiation and maintenance of immune tolerance remain to be determined . Longitudinal monitoring of peripheral chimerism, in the current study, revealed that despite a viable intragraft BM component, chimerism levels were steadily declining over time.…”
Section: Discussionmentioning
confidence: 63%
“…The level and duration of hematopoietic chimerism required to achieve transplantation tolerance have not been completely elucidated. Equally, the relative contributions of central thymic deletion versus peripheral regulatory mechanisms of host alloreactive lymphocytes to the initiation and maintenance of immune tolerance remain to be determined . Longitudinal monitoring of peripheral chimerism, in the current study, revealed that despite a viable intragraft BM component, chimerism levels were steadily declining over time.…”
Section: Discussionmentioning
confidence: 63%
“…Allogeneic HCT promotes donor‐specific immune tolerance and subsequently decreases the risk for acute and chronic graft rejection in recipients of solid organ transplants . Successful conveyance of allograft immune tolerance in the nonmyeloablative HSCT setting with persistent mixed chimerism and complete withdrawal of immunosuppressive drugs has already been shown in renal transplant recipients .…”
Section: Introductionmentioning
confidence: 99%
“…Some groups have worked for many years to develop methods to achieve tolerance to solid organ transplants by hematopoietic cell transplantation, aiming at mixed or complete chimerism [7,8,14,19,[22][23][24]28,29]. The aim would be to avoid life-long immunosuppressive treatment with its adverse effects.…”
Section: Clinical Articlesmentioning
confidence: 99%